Late Paleozoic Shoshonitic Magmatism in the Southwestern Middle Tianshan (Tajikistan) of the Southwestern Altaids: Implications for Slab Roll-Back With Extensional Arc-Related Basins After Flat Subduction - Khalimov, Gufron; Yang, He; Sang, Miao; Xiao, Wenjiao; Mamadjanov, Yunus; Aminov, Jovid; Yogibekov, Dzhovid; Liu, Xijun (Frontiers in Earth Science, 2022)
Paleozoic magmatic rocks are widespread in the western Middle Tianshan. Their petrogenesis can provide important insights into the geodynamic evolution of the southwestern Altaids. Here, we present an integrated study of U–Pb zircon geochronology, geochemical and Lu–Hf isotopic compositions for the Late Paleozoic shoshonitic Chorukhdairon pluton and genetically and spatially related quartz porphyry in the southern Chatkal-Kuram Terrane, western Middle Tianshan. The Chorukhdairon pluton mainly comprises monzodiorite and quartz monzodiorite (first phase), quartz monzonite (second and main phase), monzogranite (third phase) and leucomonzogranite (fourth phase). LA-ICP-MS zircon dating yielded magma crystallization ages of 294–291 Ma and 286 Ma for the Chorukhdairon pluton and quartz porphyry, respectively. All the rocks possess high K2O contents (3.29-5.90 wt.%) and show an affinity with shoshonite series rocks. They display similar trace element compositions characterized by enrichment of large ion lithophile elements (e.g., Rb, Th, U and K) and depletion of high field strength elements (e.g., Nb, Ta, P and Ti), compatible to typical arc magmatism. Combined with zircon Lu-Hf isotopic data, we suggest that the Chorukhdairon pluton was produced by partial melting of enriched mantle, followed by fractional crystallization of pyroxenes, amphibole, plagioclase, biotite and accessory Fe-Ti oxides, apatite and zircon. The quartz porphyries are similar to highly fractionated I-type granitic rocks and their parental magma could result from mixing of different batches of mantle-derived magmas or magmas derived from mantle and juvenile lower crust. Considering the continuousness of the Middle Carboniferous to Early Permian magmatism in the western Middle Tianshan and other regional geological data, we suggest that the Chorukhdairon pluton and related quartz porphyry probably formed in an oceanic subduction setting. Furthermore, the temporal and spatial evolution of the Paleozoic magmatism imply that the flat-slab subduction that was induced by the subduction/accretion of seamounts probably occurred beneath the Middle Tianshan during the Middle Devonian to Early Carboniferous, after which the southeastward slab roll-back occurred during the Middle Carboniferous to Early Permian. The late slab roll-back was responsible for the southeastward arc magmatism migration and magmatic flare-up in the Chatkal-Kurama terrane, western Tianshan, and led to significant crustal growth in the southwestern Altaids.